The Influence of Agency Conflict Types I and II on Earnings Management - Ratnawati, Vince; Abdul-Hamid, Mohamad Ali; Popoola, Oluwatoyin Muse Johnson (International Journal of Economics and Financial Issues, 2016)
This study examined the influence of agency conflict Type I (as represented by managerial ownership and institutional ownership), and agency conflict Type II (as represented by Control Rights, Cash Flow Rights, Cash Flow Rights leverage) on earnings management. A model was developed and tested using a sample of 108 pyramidal structure companies listed on Indonesian Stock Exchange from 2008 to 2012. Data were collected and analysed using least square regression model. The result showed that there is a significant association between managerial ownership and Control Rights. However, Control Rights (in agency conflict Type II) have the greatest influence on earnings management. Consequently, Type II agency conflict have the largest influence on earnings management compared to Type I agency conflict. The significance of the study is the potentials to assist the institutions and investors know the actual company performance and provides a better understanding of the agency theory more broadly vis-a-vis the relative impacts of Type I and Type II agency conflicts. Keywords: Earnings management, Agency conflict Type I and Type II, Developing nation JEL Classifications: G32, G23, M410